Evaluation of E.coli losses in a tidal river network using a refined 1-D numerical model. (October 2018) - Huang, Guoxian; Falconer, Roger A.; Lin, Binliang
Abstract: Predicting the rate of Escherischia coli (E.coli) loss in a river network is one of the key conditions required in the management of bathing waters, with well verified numerical models being effective tools used to predict bathing water quality in regions with limited field data. In this study, a unique finite volume method (FVM) one-dimensional model is firstly developed to solve the mass transport process in river networks, with multiple moving stagnation points. The model is then applied to predict the concentration distribution of E.coli in the river Ribble network, UK, where the phenomena of multiple stagnation points and different flow directions appear extensively in a tidal sub-channel network. Validation of the model demonstrates that the proposed method gives reasonably accurate solution. The verification results show that the model predictions generally agree well with measured discharges, water levels and E.coli concentration values, with mass conservation of the solution reaching 99.0% within 12 days for the Ribble case. An analysis of 16 one-year scenario runs for the Ribble network shows that the main reduction in E.coli concentrations occurs in the riverine and estuarine regions due to the relatively large decay rate in the brackish riverine waters and the long retention time, due to the complex river discharge patterns and the tidal flows in the regions. Highlights: A FVM scheme is used to enhance mass conservation of a mass transport model. A new algorithm is developed to track multiple stagnation points in river networks. More accurate predictions of E.coli loss rates are predicted in riverine reaches. Typically 16–48% of the E.coli die off in the Ribble river networks. E.coli fate is closely linked to source positions and transport and decay processes.